Inovasi Layanan Publik Melalui Sistem Informasi Guru "SIGUTAJAR" dan Pengembangab E- Learning di Dinas Pendidikan Kabupaten Tulungagung - Cahyono, Anang Sugeng; Cahya, Helsa Adnanda Satria; Wijaya, Erik; Ramadhani, Maulvy Aulya (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
This research analyzes public service innovation through the implementation of the Tulungagung Teacher Information System (SIGUTAJAR) and the development of e-learning platforms at the Education Office of Tulungagung Regency. Employing a qualitative library research method, this study explores system design, factors influencing implementation effectiveness, and its impact on education service quality and teacher professionalism. Research findings indicate that SIGUTAJAR has successfully integrated personnel administrative aspects with a digital learning ecosystem, creating a secure, accurate, and accessible system for various stakeholders. Adequate technological infrastructure, human resource competency in information technology, and regional leadership support serve as determinants of successful implementation. However, teachers' digital literacy gaps, application user-friendliness limitations, and system instability remain challenges requiring continuous improvement. The positive impact of this innovation manifests in improved administrative efficiency, data management transparency, and optimization of teachers' time to focus on enhancing learning quality. This research concludes that the sustainability of digital public service innovation in the education sector requires infrastructure investment, continuous capacity development, and periodic evaluation to ensure responsiveness to user needs.